Pengembangan Sistem Informasi Keuangan Masjid untuk Bidang Keuangan Fuqara Wa Masakin dan Pembangunan Masjid (Kasus: Masjid Ibnu Sina Jl. Veteran, Malang) - Ihramsyah Faishal Sugiyartomo; Ismiarta Aknuranda; Kariyoto Kariyoto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Ibnu Sina Mosque is one of the mosques in Malang City which has many activities, including the management of mosque finances. The financial management of the mosque is divided into several wallets, one of which is the fuqara wa masakin wallet which focuses on empowering the poor and the lives of fellow Muslim households. Another type of wallet is a development wallet that focuses on the provision of mosque infrastructure. This activity is a form of transparency in managing congregational money. Over time, there are problems in the wallet financial management process, namely financial records and financial data that are prone to loss because they still use printed media. Based on these problems, this project aims to build a financial information system that can help simplify the financial management process in mosque wallets. In making the system, the framework used is laravel with the aim of facilitating development to apply an object-oriented approach. This system development method uses an iterative model approach. Then the system is tested using validation testing and usability testing. Validation testing provides valid results and usability testing shows that the system is easy to use. The results of this study are expected to provide a financial information system that can help and manage mosque finances.